2007
DOI: 10.3200/jach.56.3.247-254
|View full text |Cite
|
Sign up to set email alerts
|

Staying Safe While Consuming Alcohol: A Qualitative Study of the Protective Strategies and Informational Needs of College Freshmen

Abstract: A harm-reduction focus that acknowledges and builds on existing protective strategies may be a promising avenue for alcohol interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 5 publications
7
71
1
4
Order By: Relevance
“…We also were interested in gender and typical drinking as potential factors associated with helping, as well as whether these factors might moderate the infl uence of predictors of helping. Consistent with previous research, we expected that men would drink more than women (Johnston et al, 2005;O'Malley and Johnston, 2002;Read et al, 2002;Valliant and Scanlan, 1996;Wechsler et al, 1994) and that women would engage in more helping behaviors, consistent with Howard et al (2007). Regarding typical drinking, we hypothesized that heavier drinkers would report more helping behaviors, because they would be more likely to witness heavier drinking.…”
Section: Aims and Hypothesessupporting
confidence: 73%
See 1 more Smart Citation
“…We also were interested in gender and typical drinking as potential factors associated with helping, as well as whether these factors might moderate the infl uence of predictors of helping. Consistent with previous research, we expected that men would drink more than women (Johnston et al, 2005;O'Malley and Johnston, 2002;Read et al, 2002;Valliant and Scanlan, 1996;Wechsler et al, 1994) and that women would engage in more helping behaviors, consistent with Howard et al (2007). Regarding typical drinking, we hypothesized that heavier drinkers would report more helping behaviors, because they would be more likely to witness heavier drinking.…”
Section: Aims and Hypothesessupporting
confidence: 73%
“…Students were less likely to intervene when they felt less powerful, they were drunk themselves, or they were afraid of how the intervention would affect their relationship with their peers. Finally, with respect to gender, previous research suggests women engage in more personal protective behaviors (Delva et al, 2004) and are more likely to help another person in trouble with alcohol (Howard et al, 2007).…”
Section: Helping Behaviormentioning
confidence: 99%
“…In a qualitative study of the use of protective behaviors, Howard and colleagues (2007) found that women highlighted the importance of developing a plan for the night. 40 Their plans often included presetting limits on alcohol consumption and ensuring a friend monitored their consumption. These strategies are similar to those reported more often by women in our survey and highlight the importance of planning for women.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that women ascribe more value to protective strategies in general, as they more strongly emphasize the importance of staying safe while drinking and caring for others who drink too much, while men are more hesitant to employ PBS for themselves and others (Howard, Griffin, Boekeloo, Lake, & Bellows, 2007).Thus, planning ahead of time to use PBS varies by respondent's sex, with females more likely to do so. This gender difference in PBS usage may also point to the pervasiveness of cultural double standards that more strongly emphasize college women's personal responsibility and planning while drinking to avoid adverse consequences, such as sexual victimization (Kimble, Neacsiu, Flack, & Horner, 2008).…”
Section: Discussionmentioning
confidence: 99%